Pemanfaatan Gform Dan Gboard untuk Tes Online Berbasis Handphone Android - Asra Idriyansyah Purba; Yunasdi Yunasdi (Universitas Islam Negeri Sumatera Utara, 2021)
AbstractThe purpose of this community service is to train teachers to use the GForm and GBoard applications in Online Tests. The target of this training is all Islamic religious education teachers and Madrasah teachers. It is expected from this training that teachers are better able to use handphone in online learning. This training using online training with training media using Telegram and Google Classroom, where the participants involved must be able to actively participate in activities and be able to use the GForm and GBoard applications in Online Tests. The results showed that there was a change in ability among 206 teachers regarding using the GForm and GBoard applications in Online Tests. Among them, there are 123 teachers who are able to use GForm and GBoard for online tests in the following aspects (1) Socialization and Schedule Sharing, (2) Submission of Materials and Assignment and (3) Discussion (4) Evaluation. Meanwhile, 83 people did not attend this training